Preparation method of anti-static laminate flooring

The method of impregnating papers with antistatic glue and wax coating addresses static-related dust accumulation on wooden floors, resulting in an antistatic laminate floor with enhanced cleaning and durability.

CN119192512APending Publication Date: 2024-12-27CHANGZHOU BEMATE HOME TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410992978.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-07-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional wooden floor glues generate static electricity, causing dust accumulation and difficulty in cleaning due to adhesion.

Method used

A method involving impregnating wear-resistant paper, decorative paper, and balancing paper with antistatic impregnating glue, followed by hot-pressing and coating with antistatic wax to create an antistatic laminate floor.

Benefits of technology

The method produces an antistatic laminate floor that prevents dust adhesion due to static electricity, ensuring easy cleaning and improved durability.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the technical field of floor manufacturing, in particular to a preparation method of an anti-static laminate floor. The preparation method of the anti-static laminate flooring is based on a flooring preparation process, an anti-static agent is added into the flooring through a dipping process, and then the anti-static performance of the flooring is improved through the mode. The preparation method of the anti-static laminate flooring comprises the following steps: impregnating wear-resistant paper, decorative paper and balance paper to obtain impregnated wear-resistant paper, impregnated decorative paper and impregnated balance paper; the impregnated wear-resistant paper, the impregnated decorative paper, the base plate and the impregnated balance paper are sequentially stacked and subjected to hot press molding, and the anti-static laminate flooring is obtained. Wherein the wear-resistant paper and the balance paper are subjected to gum dipping treatment by adopting antistatic dipping gum. The preparation method of the anti-static laminate flooring is used for preparing the anti-static laminate flooring with excellent anti-static effect and anti-static stability, so that dust is prevented from being adhered to the flooring due to static electricity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of floor production, and in particular to a method for preparing an anti-static laminate floor. Background Art

[0002] At present, with the change of people's consumption concept, wooden floor is becoming more and more popular. The original crafts of wooden floor mostly use spraying paint and rolling paint, but these two crafts have been replaced by floor glue. Most of the floor glues are easy to generate static electricity and adhere to dust when used on wooden floor, which makes the floor easy to accumulate dust and difficult to clean. Summary of the invention

[0003] The present application provides a method for preparing an anti-static laminate floor to improve the above-mentioned problems.

[0004] The present invention is specifically as follows:

[0005] A method for preparing an antistatic laminate floor, comprising:

[0006] Impregnating the wear-resistant paper, the decorative paper and the balancing paper with glue to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper;

[0007] Impregnated wear-resistant paper, impregnated decorative paper, base plate and impregnated balancing paper are stacked in sequence and hot-pressed to obtain an antistatic laminate floor;

[0008] Among them, wear-resistant paper and balance paper are both impregnated with antistatic impregnating glue.

[0009] In one embodiment of the present invention, when the impregnated wear-resistant paper, the impregnated decorative paper, the substrate and the impregnated balancing paper are stacked in sequence and hot-pressed, the hot-pressing temperature of the hot press is 170-220°C, the hot-pressing time is 20-60s, and the pressure is 16-25Mpa.

[0010] In one embodiment of the present invention, after the antistatic laminate floor is obtained, the method for preparing the antistatic laminate floor further comprises:

[0011] Cut the anti-static laminate floor into small pieces according to processing needs, and place the boards on the stacking machine for stacking. The stacking curing time is 5-7 days;

[0012] After curing, the wood board is slotted and shaped by four-sided planing and transverse double-end milling.

[0013] The obtained wood board is coated with chamfer paint, and the cut edge of the side is sprayed with water-resistant wax, the wax box temperature is 120-140℃, and the spraying amount is 20-25g / ㎡;

[0014] Among them, the water-resistant wax includes waterproof wood wax oil, semi-refined paraffin and antistatic agent ASSD100, and the ratio of waterproof wood wax oil, semi-refined paraffin and antistatic agent ASSD100 is 5:5:1.

[0015] In one embodiment of the present invention, before the step of impregnating the wear-resistant paper, the decorative paper and the balancing paper to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper, the method for preparing the antistatic laminate flooring further comprises:

[0016] A polymer antistatic agent is introduced into the original impregnated rubber to obtain an antistatic impregnated rubber.

[0017] In one embodiment of the present invention, the antistatic agent is ASSD100. When the antistatic agent is introduced into the impregnated original rubber for mixing, the mass ratio of the antistatic agent to the impregnated original solution is 2-5:100, and the liquid temperature during mixing is 90-100°C, and the mixing is performed for 20-30 minutes.

[0018] In one embodiment of the present invention, the preparation steps of impregnated raw rubber include:

[0019] The pH value of the formaldehyde aqueous solution is adjusted to 8-9 and then mixed with melamine for reaction for 20-30 minutes;

[0020] After adjusting the pH value to 8-8.5, the temperature was raised to 95-100°C and reacted for 60-90 minutes;

[0021] Wherein, when the formaldehyde aqueous solution and melamine are mixed and reacted, a stabilizer is added, and the stabilizer is diethylene glycol.

[0022] In one embodiment of the present invention, the preparation step of impregnating the original rubber further comprises:

[0023] After the formaldehyde aqueous solution is mixed with melamine for 20-30 minutes, the temperature is first raised to 70-80°C and a formaldehyde remover is added, and then the pH value is adjusted to 8-8.5. The formaldehyde remover includes one or more of ethylene urea, chitin, bioenzyme formaldehyde remover and photocatalyst formaldehyde remover.

[0024] In one embodiment of the present invention, the steps of preparing the antistatic impregnated adhesive include:

[0025] Mix 30-55 parts of 35%-45% formaldehyde with 10-20 parts of distilled water, add an appropriate amount of 20-35% sodium hydroxide solution, and adjust the pH to 8-9;

[0026] Then add 3-5 parts of 92%-98% diethylene glycol and 30-45 parts of melamine, stir for 20-30 minutes, then slowly heat to 70-80°C, add 1-3 parts of formaldehyde remover, and adjust the pH to 8-8.5 with sodium hydroxide;

[0027] Then continue to heat up to 95-100℃, keep warm for 60-90 minutes, cool down to 85-90℃, add 2-5 parts of antistatic agent ASSD100, stir and keep warm for 20-30 minutes, cool to room temperature to obtain antistatic impregnated glue.

[0028] In one embodiment of the present invention, the preparation steps of the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper include:

[0029] The wear-resistant paper, the decorative paper and the balance paper are immersed in the glue respectively, and after being taken out, they are pre-cured to form the dipped paper with a pre-curing degree of 30-60%;

[0030] Pre-curing is to add curing agent to the glue and treat it at 85-95℃ for 2-5min. The mass ratio of curing agent added to the mass of glue is 0.1-0.5:100.

[0031] Among them, the curing agent is one or more of MF curing agent -710, MF curing agent -740, MF curing agent -21133, and the added amount is 0.3%; the glue impregnation amount of wear-resistant paper, decorative paper and balance paper is 120-260g / m3; the glue weight of impregnated wear-resistant paper is 100-150g / cm3, and the thickness is 0.1-0.4mm; the glue weight of impregnated decorative paper is 140-170g / cm3, and the thickness is 0.1-0.4mm; the thickness of the substrate is 8-12mm, and the density is 0.5-1.0g / cm3; the glue weight of impregnated balance paper is 220-260g / cm3, and the thickness is 0.2-0.5mm.

[0032] In one embodiment of the present invention, the steps of preparing the substrate include:

[0033] The plant raw material is crushed to a particle size of 1-3 mm, and a sulfamic acid solution of 40-45% by weight of the fiber is added to the crushed fiber, with a concentration of 65-75 mg / L, and the mixture is stirred evenly, and allowed to stand for 2-3 days to soak, and the wet crushed fiber is freeze-dried to a water content of 5-7% to obtain dry fiber;

[0034] Add acetic acid solution to the dry fiber, the weight of the acetic acid solution is 20-25% of the weight of the dry fiber, stir evenly, and let it stand at room temperature and pressure for 20-24 hours; then add sodium hydroxide solution, the weight of the sodium hydroxide solution is 40-45% of the weight of the dry fiber, stir evenly, let it stand for 8-10 hours, and dry to a moisture content of 8-10% to obtain acid-base treated fiber; wherein the ratio of trees to straw in the dry fiber is 4:1, the volume concentration of the acetic acid solution is 3-5%, and the concentration of the sodium hydroxide solution is 32-36 mg / L;

[0035] The acid-base treated fiber is placed in a heating kettle, the vacuum degree is adjusted to -85--90 kPa, heated to 270-290°C at a rate of 2-3°C / min, kept warm for 30-40 minutes, adjusted to normal pressure, kept warm for 15-25 minutes, and naturally cooled to 50-70°C to obtain high pressure treated fiber;

[0036] The antistatic adhesive is uniformly added to the high-pressure treated fiber, and stirred to obtain the sizing treated fiber; wherein the amount of the antistatic adhesive added is 16-18% of the dry fiber weight; the antistatic adhesive comprises 42-44 parts of chlorinated polypropylene resin, 27-29 parts of polysilicon nitrogen resin, 21-23 parts of acrylic emulsion, 16-18 parts of polydimethylsiloxane, 5-7 parts of nano zinc oxide and 15-20 parts of antistatic agent ASSD100;

[0037] The sizing treated fiber is laid out and formed, and the obtained blank is hot pressed at a pressure of 60-65MPa. It is first heated to 220-240℃ at a speed of 2-3℃ / min, kept warm for 25-35min, then slowly cooled to 170-190℃, kept warm for 15-20min, and the density is 860-900kg / m 3 Antistatic high density fiberboard.

[0038] The beneficial effects of the present invention are:

[0039] The method for preparing an antistatic laminate floor comprises: impregnating wear-resistant paper, decorative paper and balancing paper to obtain impregnated wear-resistant paper, impregnated decorative paper and impregnated balancing paper; stacking the impregnated wear-resistant paper, impregnated decorative paper, substrate and impregnated balancing paper in sequence, and hot pressing to obtain an antistatic laminate floor; wherein the wear-resistant paper and the balancing paper are both impregnated with antistatic impregnating glue. The method for preparing an antistatic laminate floor is used to prepare an antistatic laminate floor with excellent antistatic effect and antistatic stability, so as to prevent dust from adhering to the floor due to static electricity. DETAILED DESCRIPTION

[0040] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0041] Therefore, the following detailed description of the embodiments of the present application provided is not intended to limit the scope of the present application for protection, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0042] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other.

[0044] In the description of the embodiments of the present application, it should be noted that the indicated orientation or positional relationship is the orientation or positional relationship in which the product of the application is usually placed when in use, or the orientation or positional relationship commonly understood by those skilled in the art, or the orientation or positional relationship in which the product of the application is usually placed when in use, which is only for the convenience of describing the present application and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as a limitation on the present application. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0045] In the description of the embodiments of the present application, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a direct connection or an indirect connection through an intermediate medium. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to specific circumstances.

[0046] This embodiment provides a method for preparing an anti-static laminate floor, comprising:

[0047] Impregnating the wear-resistant paper, the decorative paper and the balancing paper with glue to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper;

[0048] Impregnated wear-resistant paper, impregnated decorative paper, base plate and impregnated balancing paper are stacked in sequence and hot-pressed to obtain an antistatic laminate floor;

[0049] Among them, wear-resistant paper and balance paper are both impregnated with antistatic impregnating glue.

[0050] The principle of the preparation method of the anti-static laminate floor is:

[0051] The method for preparing the antistatic laminate floor is based on the floor preparation process, and an antistatic agent is added to the floor through an impregnation process, thereby improving the antistatic performance of the floor in this way. The method comprises: impregnating wear-resistant paper, decorative paper and balancing paper to obtain impregnated wear-resistant paper, impregnated decorative paper and impregnated balancing paper; stacking the impregnated wear-resistant paper, impregnated decorative paper, substrate and impregnated balancing paper in sequence, and hot pressing to obtain an antistatic laminate floor; wherein the wear-resistant paper and the balancing paper are both impregnated with antistatic impregnated glue. The method for preparing the antistatic laminate floor is used to prepare an antistatic laminate floor with excellent antistatic effect and antistatic stability, so as to avoid dust adhesion to the floor due to static electricity.

[0052] Furthermore, in this embodiment, when the impregnated wear-resistant paper, the impregnated decorative paper, the substrate and the impregnated balancing paper are stacked in sequence and hot-pressed, the hot-pressing temperature of the hot press is 170-220°C, the hot-pressing time is 20-60s, and the pressure is 16-25Mpa.

[0053] After the antistatic laminate floor is obtained, the steps of the preparation method of the antistatic laminate floor further include:

[0054] Cut the anti-static laminate floor into small pieces according to processing needs, and place the boards on the stacking machine for stacking. The stacking curing time is 5-7 days;

[0055] After curing, the wood board is slotted and shaped by four-sided planing and transverse double-end milling.

[0056] The obtained wood board is coated with chamfer paint, and the cut edge of the side is sprayed with water-resistant wax, the wax box temperature is 120-140℃, and the spraying amount is 20-25g / ㎡;

[0057] Among them, the water-resistant wax includes waterproof wood wax oil, semi-refined paraffin and antistatic agent ASSD100, and the ratio of waterproof wood wax oil, semi-refined paraffin and antistatic agent ASSD100 is 5:5:1.

[0058] In addition, before the step of impregnating the wear-resistant paper, the decorative paper and the balancing paper to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper, the method for preparing the antistatic laminate flooring further comprises:

[0059] A polymer antistatic agent is introduced into the original impregnated rubber to obtain an antistatic impregnated rubber.

[0060] It should be noted that the polymer antistatic agent uses the permanent antistatic agent ASSD100 from DuPont, USA, which is suitable for ABS, PVC, PS and other resins. When the antistatic agent is ASSD100, when the antistatic agent is introduced into the impregnated original rubber for mixing, the antistatic effect can be ensured by controlling the amount added. The mass ratio of the antistatic agent to the impregnated original solution is 2-5:100, and the liquid temperature during mixing is 90-100℃, and the mixing time is 20-30min.

[0061] Based on the above content, in this embodiment, the preparation steps of impregnated raw rubber include:

[0062] The pH value of the formaldehyde aqueous solution is adjusted to 8-9 and then mixed with melamine for reaction for 20-30 minutes;

[0063] After adjusting the pH value to 8-8.5, the temperature was raised to 95-100°C and reacted for 60-90 minutes;

[0064] When the formaldehyde aqueous solution and melamine are mixed and reacted, a stabilizer is added, and the stabilizer is diethylene glycol. By introducing the stabilizer, the stability of the prepared adhesive is better, which is conducive to further extending the service life of the floor.

[0065] It should be noted that the pH of the reaction needs to be precisely controlled during the reaction so that melamine maintains good reactivity.

[0066] Furthermore, in this embodiment, the preparation step of impregnating the original rubber also includes:

[0067] After the formaldehyde aqueous solution is mixed with melamine for 20-30 minutes, the temperature is first raised to 70-80°C and a aldehyde remover is added, and then the pH value is adjusted to 8-8.5. The aldehyde remover includes one or more of ethylene urea, chitin, biological enzyme aldehyde remover and photocatalyst aldehyde remover. The heating process adopts a slow heating method, and the formaldehyde content in the adhesive is reduced by adding the aldehyde remover to meet the requirements of environmental protection. The specific composition of the aldehyde remover is not limited, and it can be, for example, ethylene urea, chitin, biological enzyme aldehyde remover, photocatalyst aldehyde remover, etc.

[0068] In this embodiment, the steps of preparing the antistatic impregnated adhesive include:

[0069] Mix 30-55 parts of 35%-45% formaldehyde with 10-20 parts of distilled water, add an appropriate amount of 20-35% sodium hydroxide solution, and adjust the pH to 8-9;

[0070] Then add 3-5 parts of 92%-98% diethylene glycol and 30-45 parts of melamine, stir for 20-30 minutes, then slowly heat to 70-80°C, add 1-3 parts of formaldehyde remover, and adjust the pH to 8-8.5 with sodium hydroxide;

[0071] Then continue to heat up to 95-100℃, keep warm for 60-90 minutes, cool down to 85-90℃, add 2-5 parts of antistatic agent ASSD100, stir and keep warm for 20-30 minutes, cool to room temperature to obtain antistatic impregnated glue.

[0072] It should be noted that, in this embodiment, the wear-resistant paper, the decorative paper and the balancing paper are impregnated with glue to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper, wherein the wear-resistant paper and the balancing paper are impregnated with antistatic impregnating glue, and the glue used in the impregnation process of the decorative paper is not limited, and can be a general commercially available impregnating glue, thus, the impregnated paper is impregnated with the antistatic impregnating glue and then pressed to improve the antistatic durability. The preparation steps of the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper include:

[0073] The wear-resistant paper, the decorative paper and the balance paper are immersed in the glue respectively, and after being taken out, they are pre-cured to form the dipped paper with a pre-curing degree of 30-60%;

[0074] Pre-curing is to add curing agent to the glue and treat it at 85-95℃ for 2-5min. The mass ratio of curing agent added to the mass of glue is 0.1-0.5:100.

[0075] Among them, the curing agent is one or more of MF curing agent -710, MF curing agent -740, MF curing agent -21133, and the added amount is 0.3%; the glue impregnation amount of wear-resistant paper, decorative paper and balance paper is 120-260g / m3; the glue weight of impregnated wear-resistant paper is 100-150g / cm3, and the thickness is 0.1-0.4mm; the glue weight of impregnated decorative paper is 140-170g / cm3, and the thickness is 0.1-0.4mm; the thickness of the substrate is 8-12mm, and the density is 0.5-1.0g / cm3; the glue weight of impregnated balance paper is 220-260g / cm3, and the thickness is 0.2-0.5mm.

[0076] It should be noted that the pre-curing process can be carried out in a drying oven in a conventional manner.

[0077] In this embodiment, the substrate is a laminate floor, and the raw materials are trees, crop straw, aminosulfonic acid solution, acetic acid solution, sodium hydroxide solution, and adhesive. The steps of preparing the substrate include:

[0078] The plant raw material is crushed to a particle size of 1-3 mm, and a sulfamic acid solution of 40-45% by weight of the fiber is added to the crushed fiber, with a concentration of 65-75 mg / L, and the mixture is stirred evenly, and allowed to stand for 2-3 days to soak, and the wet crushed fiber is freeze-dried to a water content of 5-7% to obtain dry fiber;

[0079] Add acetic acid solution to the dry fiber, the weight of the acetic acid solution is 20-25% of the weight of the dry fiber, stir evenly, and let it stand at room temperature and pressure for 20-24 hours; then add sodium hydroxide solution, the weight of the sodium hydroxide solution is 40-45% of the weight of the dry fiber, stir evenly, let it stand for 8-10 hours, and dry to a moisture content of 8-10% to obtain acid-base treated fiber; wherein the ratio of trees to straw in the dry fiber is 4:1, the volume concentration of the acetic acid solution is 3-5%, and the concentration of the sodium hydroxide solution is 32-36 mg / L;

[0080] The acid-base treated fiber is placed in a heating kettle, the vacuum degree is adjusted to -85--90 kPa, heated to 270-290°C at a rate of 2-3°C / min, kept warm for 30-40 minutes, adjusted to normal pressure, kept warm for 15-25 minutes, and naturally cooled to 50-70°C to obtain high pressure treated fiber;

[0081] The antistatic adhesive is uniformly added to the high-pressure treated fiber, and the mixture is stirred to obtain the sizing treated fiber; wherein the amount of the antistatic adhesive added is 16-18% of the dry fiber weight; the antistatic adhesive comprises 42-44 parts of chlorinated polypropylene resin, 27-29 parts of polysilicon nitrogen resin, 21-23 parts of acrylic emulsion, 16-18 parts of polydimethylsiloxane, 5-7 parts of nano zinc oxide, and 15-20 parts of antistatic agent ASSD100; this method can improve the bonding ability between fibers, increase the strength of the density board, and at the same time improve the hydrophobic, antistatic and antibacterial properties of the density board, delay the aging of the density board, and extend the service life of the density board, and the sizing treated fiber is uniformly stirred;

[0082] The sizing treated fibers are laid out and formed, and the obtained blanks are hot pressed at a pressure of 60-65MPa. They are first heated to 220-240℃ at a speed of 2-3℃ / min and kept warm for 25-35min to promote the antistatic adhesive in the density board to adhere evenly to the surface of the crushed fibers. At the same time, the moisture in the adhesive can be removed to increase the bonding ability between the crushed fibers. Then the temperature is slowly lowered to 170-190℃ and kept warm for 15-20min to promote the uniform film formation of the antistatic adhesive and improve the adhesive ability. The temperature is naturally lowered to room temperature to uniformly solidify the antistatic adhesive in the density board, increase the strength and wear resistance of the density board, and obtain a density of 860-900kg / m 3 Antistatic high-density fiberboard is the base board.

[0083] In summary, the steps of making a substrate in the method for preparing an antistatic laminate floor are as follows:

[0084] Step 1, crushing the plant raw material to a particle size of 1-3 mm, adding 40-45% of the fiber weight of aminosulfonic acid solution (concentration of 65-75 mg / L) to the crushed fiber, stirring evenly, standing and soaking for 2-3 days, and freeze-drying the wet crushed fiber to a water content of 5-7% to obtain dry fiber;

[0085] Step 2, adding acetic acid solution (volume concentration of 3-5%) of 20-25% of the weight of the dry fiber to the dry fiber (the ratio of trees to straw is 4:1), stirring evenly, standing at room temperature and pressure for 20-24 hours, then adding sodium hydroxide solution (concentration of 32-36 mg / L) of 40-45% of the weight of the dry fiber, stirring evenly, standing for 8-10 hours, and drying to a moisture content of 8-10%, thereby obtaining acid-base treated fiber;

[0086] Step 3, placing the acid-base treated fiber in a heating kettle, adjusting the vacuum degree to -85--90 kPa, heating to 270-290°C at a rate of 2-3°C / min, keeping the temperature for 30-40 minutes, adjusting to normal pressure, keeping the temperature for 15-25 minutes, and naturally cooling to 50-70°C to obtain high pressure treated fiber;

[0087] Step 4, evenly adding antistatic adhesive (raw materials are chlorinated polypropylene resin 42-44, polysilicon nitrogen resin 27-29, acrylic emulsion 21-23, polydimethylsiloxane 16-18, nano zinc oxide 5-7, 15-20 antistatic agent ASSD100) to the high-pressure treated fiber, the added amount is 16-18% of the dry fiber weight, which can improve the bonding ability between fibers, increase the strength of the density board, and also improve the hydrophobicity, antistatic performance and antibacterial performance of the density board, delay the aging of the density board, and extend the service life of the density board, and stir evenly to obtain the sizing treated fiber;

[0088] Step 5: Lay the sizing treated fibers and perform hot pressing on the obtained blank at a pressure of 60-65MPa. First, heat to 220-240°C at a rate of 2-3°C / min and keep warm for 25-35min to promote the antistatic adhesive in the density board to adhere evenly to the surface of the crushed fibers. At the same time, it can remove moisture in the adhesive and increase the bonding ability between the crushed fibers. Then slowly reduce the temperature to 170-190°C and keep warm for 15-20min to promote the uniform film formation of the antistatic adhesive and improve the adhesive ability. Then, naturally reduce the temperature to room temperature to uniformly solidify the antistatic adhesive in the density board, increase the strength and wear resistance of the density board, and obtain a density of 860-900kg / m 3 Antistatic high-density fiberboard;

[0089] Step 6, the wear-resistant paper, balancing paper and decorative paper cut to appropriate sizes are sequentially pressed on the high-density substrate plate by a hot press, which are balancing paper, substrate, decorative paper and wear-resistant paper from bottom to top, and the hot pressing temperature of the hot press is 170-220°C, the hot pressing time is 20-60s, and the pressure is 18-25Mpa;

[0090] Step 7, after cooling for 24 hours, the board is cut into small pieces according to processing needs, and the small pieces of wood are stacked on a stacking machine for 5-7 days to prevent the small boards from bending;

[0091] Step 9, after curing, slotting and forming are performed, and the wood board is slotted and formed by a four-sided planer and a transverse double-end milling process;

[0092] Step 10, apply chamfer paint to the obtained small pieces, spray water-resistant wax (raw materials are waterproof wood wax oil + semi-refined paraffin + antistatic agent ASSD100 in a ratio of 5:5:1) on the side cuts, the wax box temperature is 120-140°C, and the spraying amount is 20-25g / ㎡. After cutting small pieces of board and opening the tongue and groove, the front and back surfaces of the board are affixed with hot-pressed decorative wear-resistant impregnated paper and a balancing layer, which have a certain protective effect. The protective effect on the four sides of the small board is weak. By spraying water-resistant wax on the four sides after opening the tongue and groove, the protective, waterproof and anti-static effects of the four sides are enhanced.

[0093] Based on the above content, the steps of the preparation method of the anti-static laminate floor are as follows:

[0094] 30-55 parts of 35%-45% formaldehyde and 10-20 parts of distilled water are mixed evenly, and an appropriate amount of 20-35% sodium hydroxide solution is added to adjust the pH to 8-9; then 3-5 parts of 92%-98% diethylene glycol and 30-45 parts of melamine are added, stirred for 20-30 minutes, and then the temperature is slowly raised to 70-80°C, 1-3 parts of formaldehyde removal agent are added, and the pH is adjusted to 8-8.5 by sodium hydroxide, and then the temperature is continued to be raised to 95-100°C, and the temperature is kept for 60-90 minutes, and the temperature is lowered to 85-90°C, and 2-5 parts of antistatic agent ASSD100 are added, and the temperature is kept for 20-30 minutes, and the antistatic impregnated adhesive is obtained;

[0095] The wear-resistant paper, the decorative paper and the balancing paper are impregnated with glue to obtain impregnated wear-resistant paper, impregnated decorative paper and impregnated balancing paper, wherein the wear-resistant paper and the balancing paper are both impregnated with antistatic impregnating glue, and the glue used in the impregnation process of the decorative paper is not limited and can be a general commercially available impregnating glue; the impregnated paper is impregnated with the antistatic impregnating glue and then pressed to improve the antistatic durability;

[0096] The preparation process of impregnated wear-resistant paper, impregnated decorative paper and impregnated balancing paper includes: immersing the wear-resistant paper, decorative paper and balancing paper in glue respectively, taking them out and pre-curing them to form impregnated paper with a pre-curing degree of 30-60%; pre-curing is to add a curing agent to the glue and treat it at 85-95°C for 2-5 minutes, and the mass ratio of the added amount of the curing agent to the mass of the glue is 0.1-0.5:100; specifically, the curing agent is one or more of MF curing agent-710, MF curing agent-740, and MF curing agent-21133. When MF curing agent-740 is selected, the added amount is 0.3%, and the pre-curing process can be processed in a drying oven in a conventional manner; the impregnation amount of the wear-resistant paper, decorative paper and balancing paper is 120-260g / m3, the wear-resistant paper and balancing paper are impregnated with antistatic impregnating glue, and the decorative paper is impregnated with general commercially available glue such as polyurethane glue;

[0097] The weight of impregnated wear-resistant paper is (including glue) 100-150g / cm3, and the thickness is 0.1-0.4mm; the weight of impregnated decorative paper is (including glue) 140-170g / cm3, and the thickness is 0.1-0.4mm; the thickness of the base plate is 8-12mm, and the density is 0.5-1.0g / cm3; the weight of impregnated balancing paper is (including glue) 220-260g / cm3, and the thickness is 0.2-0.5mm; the amount of glue impregnation in each layer will affect the antistatic performance of the final floor;

[0098] The impregnated wear-resistant paper, impregnated decorative paper, substrate and impregnated balancing paper are sequentially arranged and hot-pressed. The specific process of hot-pressing can adopt the existing process; the operating temperature of hot-pressing is 180-200°C, and the operating pressure is 16-25MPa; the hot-pressing time of hot-pressing is 20-45s; by further optimizing the temperature, pressure and time of hot-pressing, it is beneficial to further enhance the antistatic effect and prevent the hot-pressing temperature from being too low to affect the molding effect.

[0099] Based on the above-mentioned method for preparing the antistatic laminate floor, it includes the following embodiments:

[0100] Implementation 1:

[0101] 1. Evenly mix 37 parts of 38% formaldehyde with 18 parts of distilled water, add an appropriate amount of 25% sodium hydroxide solution, and adjust the pH to 8-8.5. Then add 3.5 parts of 96% diethylene glycol and 35 parts of melamine, stir for 20 minutes, then slowly heat up to 80°C, add 1.3 parts of ethylene urea, adjust the pH to 8-8.5 with sodium hydroxide, then continue to heat up to 100°C, keep warm for 70 minutes, cool down to 90°C, add 5 parts of antistatic agent ASSD100, stir and keep warm for 30 minutes, cool to room temperature, and obtain organic antistatic impregnation glue.

[0102] 2. Add MF curing agent-740 to the impregnated glue containing antistatic agent for wear-resistant paper and balance paper, the mass ratio of curing agent added to glue is 0.5:100, and pass through 90℃ drying oven (4 minutes) to form a certain 55% pre-cured impregnated paper, the impregnated amount is 100g of wear-resistant paper and 150g of balance paper, cut and seal to obtain antistatic impregnated paper. Immerse decorative paper in melamine formaldehyde glue (i.e. glue without antistatic agent), add MF curing agent-740 to the impregnated glue, the mass ratio of curing agent added to glue is 0.5:100, pass through 85℃ drying oven (3 minutes), and form impregnated decorative paper with 40% pre-cured degree.

[0103] 3. The weight of the impregnated wear-resistant paper is (including glue) 125g / cm3, and the thickness is 0.15mm; the weight of the impregnated decorative paper is (including glue) 160g / cm3, and the thickness is 0.2mm; the thickness of the substrate is 12mm, and the density is 0.85g / cm3; the weight of the impregnated balance paper is (including glue) 240g / cm3, and the thickness is 0.3mm;

[0104] 4. The plant material is crushed to a particle size of 1-3 mm, the ratio of plant material trees to straw is 5:1, 40% of the fiber weight of aminosulfonic acid solution (concentration of 65-mg / L) is added to the crushed fiber, stirred evenly, and allowed to stand for 2 days. The wet crushed fiber is freeze-dried to a moisture content of 5-7%, which is beneficial to enhance the binding force between cellulose and lignin, avoid expansion and deformation of the density board after water absorption, keep the structure of the density board intact, and obtain dry fiber;

[0105] Add 3% acetic acid solution with a volume concentration of 20% of the weight of the dry fiber to the dry fiber, stir evenly, let it stand at room temperature and pressure for 20 hours, then add 32 mg / L sodium hydroxide with a concentration of 40% of the weight of the dry fiber, stir evenly, let it stand for 8 hours, and dry to a moisture content of 8-10%. The crushed fiber is treated with acid and alkali respectively to fix the binding force between cellulose and lignin to avoid changes in the size of the density board caused by an increase or decrease in the binding force, and at the same time reduce the water retention capacity of the crushed fiber, so that the density board can be quickly dried after being soaked in water, and the structural stability of the density board is maintained, thereby obtaining acid-alkali treated fibers.

[0106] The acid-base treated fiber is placed in a heating kettle, the vacuum degree is adjusted to -85kPa, heated to 270℃ at a speed of 2℃ / min, kept warm for 30min, adjusted to normal pressure, kept warm for 15min, naturally cooled to 50℃, and kept warm for a long time after rapid heating to make the various components in the pulverized fiber evenly mixed and penetrated, reduce the water absorption and water retention capacity of the pulverized fiber, improve the hydrophobic properties of the density board, and obtain high-pressure treated fiber.

[0107] The adhesive is evenly added into the high-pressure treated fiber. The raw materials are 42 parts of chlorinated polypropylene resin, 27 parts of polysilicon nitrogen resin, 21 parts of acrylic emulsion, 16 parts of polydimethylsiloxane, and 5 parts of nano zinc oxide. The antistatic agent ASSD100 is added in an amount of 16-18% of the dry fiber weight. This can improve the bonding ability between fibers and increase the strength of the density board. It can also improve the hydrophobic, antistatic and antibacterial properties of the density board, delay the aging of the density board, and extend the service life of the density board. The fiber is evenly stirred to obtain the sizing-treated fiber.

[0108] The sizing treated fibers were laid out and formed, and the obtained blanks were hot pressed at a pressure of 60MPa. They were first heated to 220℃ at a speed of 2℃ / min and kept warm for 25min to promote the adhesive in the density board to adhere evenly to the surface of the crushed fibers. At the same time, the moisture in the adhesive can be removed to increase the bonding ability between the crushed fibers. Then the temperature was slowly lowered to 170℃ and kept warm for 15min to promote the uniform film formation of the adhesive and improve the adhesive ability. The temperature was naturally lowered to room temperature to evenly solidify the adhesive in the density board, increase the strength and wear resistance of the density board, and obtain a density of 860-900kg / m 3 Moisture-proof and anti-static high-density fiberboard.

[0109] The antistatic laminate floor is obtained by hot pressing the wear-resistant paper, decorative paper, base material and balance paper from top to bottom at a hot pressing temperature of 200° C., a pressure of 20 MPA and a holding time of 25 seconds.

[0110] Implementation 2:

[0111] The steps are substantially the same as those in Example 1, except that the hot pressing temperature is 200° C., the pressure is 25 MPa, and the time is 35 s.

[0112] Implementation 3:

[0113] The steps are substantially the same as those in Example 1, except that the hot pressing temperature is 220° C., the pressure is 20 MPa, and the time is 15 s.

[0114] The electrostatic performance of the antistatic floor prepared by the conventional method in Examples 1-3 is shown as follows:

[0115] <![CDATA[Surface resistivity (Ω / m2)]]> Implementation Method 1 <![CDATA[8.3×10 5 ]]> Implementation Method 2 <![CDATA[8.9×10 5 ]]> Implementation 3 <![CDATA[9.1×10 5 ]]>

[0116] The above are only preferred embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.

Claims

1. A method for preparing an antistatic laminate floor, characterized in that: include: Impregnating the wear-resistant paper, the decorative paper and the balancing paper with glue to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper; The impregnated wear-resistant paper, the impregnated decorative paper, the substrate and the impregnated balancing paper are stacked in sequence and hot-pressed to obtain an antistatic laminate floor; Wherein, the wear-resistant paper and the balancing paper are both impregnated with antistatic impregnating glue.

2. The method for preparing the antistatic laminate floor according to claim 1, characterized in that: When the impregnated wear-resistant paper, the impregnated decorative paper, the substrate and the impregnated balancing paper are stacked in sequence and hot-pressed, the hot-pressing temperature of the hot press is 170-220° C., the hot-pressing time is 20-60 seconds, and the pressure is 16-25 MPa.

3. The method for preparing the antistatic laminate floor according to claim 2, characterized in that: After the antistatic laminate floor is obtained, the method for preparing the antistatic laminate floor further comprises: Cutting the antistatic laminate floor into small pieces of wood according to processing requirements, placing the wood on a stacking machine for stacking, and stacking for 5-7 days; After curing, the wood board is slotted and formed by four-sided planing and transverse double-end milling. The obtained wood board is coated with chamfer paint, and the cut edge of the side is sprayed with water-resistant wax, the wax box temperature is 120-140°C, and the spraying amount is 20-25g / ㎡; The water-resistant wax comprises waterproof wood wax oil, semi-refined paraffin wax and antistatic agent ASSD100, and the ratio of the waterproof wood wax oil, the semi-refined paraffin wax and the antistatic agent ASSD100 is 5:5:

1.

4. The method for preparing the antistatic laminate floor according to claim 1, characterized in that: Before the step of impregnating the wear-resistant paper, the decorative paper and the balancing paper to obtain the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper, the method for preparing the antistatic laminate flooring further comprises: A polymer antistatic agent is introduced into the original impregnated rubber to obtain the antistatic impregnated rubber.

5. The method for preparing the antistatic laminate floor according to claim 4, characterized in that: The antistatic agent is ASSD100. When the antistatic agent is introduced into the impregnated original rubber for mixing, the mass ratio of the antistatic agent to the impregnated original solution is 2-5:100, and the liquid temperature during mixing is 90-100° C., and the mixing is performed for 20-30 minutes.

6. The method for preparing the antistatic laminate floor according to claim 5, characterized in that: The preparation steps of the impregnated raw rubber include: The pH value of the formaldehyde aqueous solution is adjusted to 8-9 and then mixed with melamine for reaction for 20-30 minutes; After adjusting the pH value to 8-8.5, the temperature was raised to 95-100°C and reacted for 60-90 minutes; Wherein, when the formaldehyde aqueous solution and melamine are mixed and reacted, a stabilizer is added, and the stabilizer is diethylene glycol.

7. The method for preparing the antistatic laminate floor according to claim 6, characterized in that: The preparation step of the impregnated raw rubber also includes: After the formaldehyde aqueous solution is mixed with melamine for 20-30 minutes, the temperature is first raised to 70-80° C., a formaldehyde remover is added, and then the pH value is adjusted to 8-8.

5. The formaldehyde remover includes one or more of ethylene urea, chitin, bioenzyme formaldehyde remover and photocatalyst formaldehyde remover.

8. The method for preparing the antistatic laminate floor according to claim 7, characterized in that: The preparation steps of the antistatic impregnated adhesive include: Mix 30-55 parts of 35%-45% formaldehyde with 10-20 parts of distilled water, add an appropriate amount of 20-35% sodium hydroxide solution, and adjust the pH to 8-9; Then add 3-5 parts of 92%-98% diethylene glycol and 30-45 parts of melamine, stir for 20-30 minutes, then slowly heat to 70-80°C, add 1-3 parts of formaldehyde remover, and adjust the pH to 8-8.5 with sodium hydroxide; Then continue to heat up to 95-100℃, keep warm for 60-90 minutes, cool down to 85-90℃, add 2-5 parts of antistatic agent ASSD100, stir and keep warm for 20-30 minutes, cool to room temperature to obtain antistatic impregnated glue.

9. The method for preparing the antistatic laminate floor according to any one of claims 1 to 8, characterized in that: The preparation steps of the impregnated wear-resistant paper, the impregnated decorative paper and the impregnated balancing paper include: The wear-resistant paper, the decorative paper and the balancing paper are immersed in glue respectively, and after being taken out, they are pre-cured to form impregnated paper with a pre-curing degree of 30-60%; Pre-curing is to add curing agent to the glue and treat it at 85-95℃ for 2-5min. The mass ratio of curing agent added to the mass of glue is 0.1-0.5:

100. Wherein, the curing agent is one or more of MF curing agent -710, MF curing agent -740, MF curing agent -21133, and the added amount is 0.3%; the glue impregnation amount of the wear-resistant paper, the decorative paper and the balancing paper is 120-260g / m3; the glue weight of the impregnated wear-resistant paper is 100-150g / cm3, and the thickness is 0.1-0.4mm; the glue weight of the impregnated decorative paper is 140-170g / cm3, and the thickness is 0.1-0.4mm; the thickness of the substrate is 8-12mm, and the density is 0.5-1.0g / cm3; the glue weight of the impregnated balancing paper is 220-260g / cm3, and the thickness is 0.2-0.5mm.

10. The method for preparing the antistatic laminate floor according to any one of claims 1 to 8, characterized in that: The steps of preparing the substrate include: The plant raw material is crushed to a particle size of 1-3 mm, and a sulfamic acid solution of 40-45% by weight of the fiber is added to the crushed fiber, with a concentration of 65-75 mg / L, and the mixture is stirred evenly, and allowed to stand for 2-3 days to soak, and the wet crushed fiber is freeze-dried to a water content of 5-7% to obtain dry fiber; Adding acetic acid solution to the dry fiber, the weight of the acetic acid solution is 20-25% of the weight of the dry fiber, stirring evenly, and standing at room temperature and pressure for 20-24 hours; then adding sodium hydroxide solution, the weight of the sodium hydroxide solution is 40-45% of the weight of the dry fiber, stirring evenly, standing for 8-10 hours, and drying to a moisture content of 8-10%, to obtain acid-base treated fiber; wherein the ratio of trees to straw in the dry fiber is 4:1, the volume concentration of the acetic acid solution is 3-5%, and the concentration of the sodium hydroxide solution is 32-36 mg / L; The acid-base treated fiber is placed in a heating kettle, the vacuum degree is adjusted to -85--90 kPa, heated to 270-290°C at a rate of 2-3°C / min, kept warm for 30-40 minutes, adjusted to normal pressure, kept warm for 15-25 minutes, and naturally cooled to 50-70°C to obtain high pressure treated fiber; Uniformly adding antistatic adhesive to the high-pressure treated fiber, stirring uniformly to obtain sizing treated fiber; wherein the amount of the antistatic adhesive added is 16-18% of the dry fiber weight; the antistatic adhesive comprises 42-44 parts of chlorinated polypropylene resin, 27-29 parts of polysilicon nitrogen resin, 21-23 parts of acrylic emulsion, 16-18 parts of polydimethylsiloxane, 5-7 parts of nano zinc oxide and 15-20 parts of antistatic agent ASSD100; The sizing treated fiber is laid out and formed, and the obtained blank is hot pressed at a pressure of 60-65 MPa, first heated to 220-240°C at a speed of 2-3°C / min, kept warm for 25-35min, then slowly cooled to 170-190°C, kept warm for 15-20min, and obtained a density of 860-900kg / m 3 Antistatic high density fiberboard.